Between Artefacts, Fragments, and Texts: An Analysis of 4Q266 Column I. - Tucker, James M.; Porzig, Peter (Dead Sea Discoveries, 2018)
In this article, we propose a new reconstruction of column I of 4Q266 (4QD), which is part of our new edition of the Damascus Document. Our proposed reconstruction results from a careful assessment of previous reconstructions of this column, as it pertains to fragment 1b and its relationship to frag. 1a. Specifically, we argue that the DJD line 1 reading of ב]נ֯י̇ אור לה̇נז֯ר֯ מדר֯[כי is better understood as a scribal gloss and not as the first line of the column. We conclude the article by discussing the compositional history of the Damascus Document, especially in terms of how our new reconstruction relates to the Cairo Genizah Codex CD A.